Prinsip Kesetaraan Gender dan Non Diskriminasi dalam KOvenan ICESCR dan ICCPR - Wahyuningsih - (Jurnal Hukum PRIORIS, 2008)
Universal Declaration of Human Rights recognizes the inherent dignity and of the equal and inalienable rights of all members of the human family as the foundation of freedom, justice and peace in the world. To exercise those rights, in 1966 General Assembly of the UN has adopted two Covenant, namely International Covenant of Economic, Social and Cultural Rights and International Covenants on Civil and Political Rights. The States Parties of the two Covenants undertake to guarantee that the rights regulated in the covenants language, religion, political or other opinion, national or social origin, property, birth or other status. So that we can conclude that the two Covenant recognize, the existence of gender equality principle and non discrimination principle.